Building competitive strategies For shinhan bank VietNam = Xây dựng chiến lược cạnh tranh cho ngân hàng shinhan bank Việt Nam - Kim, Jihyun (2020)
This paper has a lot of attention to analytical tools and a variety of data to investigate the business environment and the other factors in order to build and propose competitive strategies for Shinhan Bank Vietnam. The general objective of the study is to investigate the trend and degree of concentration in the banking industry of Vietnam and to suggest competition strategies for Shinhan Bank Vietnam. Based on the general objectives above, the study has specific objectives as below: 1. To determine the degree of concentration in the banking industry of Vietnam. 2. To survey the theoretical and empirical literature on banking concentration and analyze the Vietnam‟s banking system from 2012 to 2018. 3. To provide competitive suggestions for Shinhan Bank Vietnam based on the investigation 1 and 2 above